A fuzzy-set qualitative comparative analysis of corruption and homicide in Organisation for Economic Co-operation and Development countries through the lens of the institutional anomie theory - Cruz, José N (European journal of criminology, 2023)
Institutional Anomie Theory has been widely used in the study of criminal phenomena. Institutional Anomie Theory offers a macro explanation of crime because it locates the cause of crime in the anomie created by the combination of a cultural overemphasis on monetary success and restricted economic opportunity. In such a context, the economy dominates the social macrostructure and non-economic social institutions (family, education, polity) may counterbalance (Merton's approach) or reinforce (Messner and Rosenfeld's approach) economic pressures. Institutional Anomie Theory has been tested with multivariate regression and with multilevel modelling. Neither of these statistical approaches addresses the question of which combinations of institutions lead to criminal behaviour. This study attempts to fill this gap by using the fuzzy-set qualitative comparative analysis which allows multiple causality and asymmetric analysis of high and low crime rates. Based on the Institutional Anomie Theory theoretical model, this study demonstrates the existence of conditions for corruption and homicide in Organisation for Economic Co-operation and Development countries. The results are generally consistent with Merton's approach. It is shown that economic pressures combined with weak social institutions condition the extent of corruption and homicide in Organisation for Economic Co-operation and Development countries. However, there are differences between the two types of crime. The results also suggest that there is no symmetry in the causal combinations between high and low crime rates. The implications of these findings are discussed.